The strategic opinion leader - Dubois, E (2015)
Opinion leaders are important political players who bridge the gap between the political elite and the general public. Traditionally opinion leaders use social pressure and social support via interpersonal communication to personally influence the opinions, attitudes and behaviours of their everyday associates (who make up the general public). However, in a hybrid media system opinion leaders have access to added channels which mean they can communicate with audiences beyond their everyday associates and/or engage in non-interpersonal interactions, potentially setting the stage for opinion leaders to become more influential since they can access more members of the general public. Conversely, since the ability of opinion leaders to influence others traditionally relies on strong social bonds, even if audiences are accessible for information transfer, the lack of social connection could mean influence does not flow. As such, opinion leaders' channel choice in a hybrid media system is potentially very important. To investigate the patterns of channel use as well as motivations for, and impacts of, channel choices by opinion leaders, a two phase mixed-methods study is employed. Phase one includes online social network analysis of the #CDNpoli (Canadian politics) hashtag on Twitter and an online survey. Phase two investigates the communication practices of 21 specific digitally enabled opinion leaders drawn from the #CDNpoli network. Two hour in-depth interviews are paired with visualizations of the participants trace data. Telephone interviews with associates (alters) of the primary interviewee were conducted (N=27). This design is therefore responsive to the multi-channel reality of a hybrid media system and improves upon large scale and single channel studies which are most common in this line of research. Now strategic and, at times, impersonal, a fundamental shift in how influence is derived challenges theories of social influence and information dissemination. Two types of strategic opinion leaders emerge: enthusiasts and champions. Their strategies contribute to a wider trend - a "just-in-time" informed citizenry - where those who do not opt in to receiving messages from the political elite only get information at the last possible minute, such as during a scandal or an election. Future research and communication strategy must be sensitive to the varied aims and tactics of digitally enabled opinion leaders as well as the subsequent inconsistent relationship between the uninformed and their political system.